Analisis Konsentrasi Industri di Indonesia (Studi Kasus Industri Semen di Indonesia) - Annisa Dwi Chusniah; Choerunisa Marlin Suryani; Difa Fachnisa; Nur Laeli Utami; Naerul Edwin Kiky Aprianto; Rifa Aulia Nur Sabani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
. Industrial concentration is an indicator in determining the level of market dominance by companies in the economic sector. This study aims to analyze the concentration level of the cement industry in Indonesia, understand the market structure, company behavior, and industrial performance. The cement industry was chosen because of its significant role in supporting national infrastructure development. The research uses a qualitative method with a literature study approach, utilizing secondary data from various literature, including journals and books. The analysis was carried out by measuring market concentration using the concentration ratio (CR4) and the Herfindahl-Hirschman index (HHI), as well as the Structure-Conduct-Performance (SCP) approach. The results of the study show that the cement industry in Indonesia has a high level of concentration, with PT. Semen Indonesia as a market leader. The market structure is classified as oligopoly, characterized by the dominance of several large companies such as PT. Semen Indonesia. Market behavior includes price competition and non-price strategies, as well as distributions focused on innovation and market share expansion. The market performance of this industry is dominated by two large companies, reflecting significant oligopoly characteristics.